Konten Visual Pengguna Media Sosial Sebagai Promosi Organik Pariwisata Pulau Gili, Lombok, Nusa Tenggara Barat - Yogantari, Made Vairagya (Indonesian Scientific Journal (Jurnal Ilmiah Indonesia), 2024)
This study aims to analyze the potential of user-generated content (UGC) in promoting tourism in Gili Islands. Employing a qualitative descriptive approach, this research identifies and analyzes visual content uploaded on social media by various tourism stakeholders in Gili Islands. Direct field surveys revealed that UGC has successfully cultivated a positive image of Gili Islands as an attractive tourist destination, particularly regarding its natural beauty, activities, and culinary experiences. This content not only serves as personal branding but also as an effective organic promotional tool in attracting potential tourists. Furthermore, the study uncovers a gap between users' technical capabilities in utilizing social media and their understanding of the potential of social media as a tourism promotion tool. Based on these findings, this study recommends further efforts to enhance the digital literacy of tourism stakeholders and encourage the optimal utilization of social media in promoting Gili Islands. Key Words: Visual content, user-generated content, social media, organic promotion, Gili Island